Legal Protection Against Children Being Victims Of Crimes Prosecution Stage In Kudus - Dedy Nurjatmiko (Jurnal Daulat Hukum, 2018)
Protection of child victims in law enforcement process is essential to ensure the fairness of the essentials, in addition to criminal punishment to the perpetrators of the crime. This study aims to determine and analyze the consideration Requisitor prosecutors of the State Prosecutor of the case the defendant Child in Kudus of the rights of child victims. The method used in this research is juridical empirical method. Specifications research the authors use the descriptive analysis. Data collected in-depth interviews with the parties involved in research, direct observation and recording of documents. The survey results revealed the consideration of the Public Prosecutor in Requisitor yet fully protect the rights, rights of the victim, such as notifying the right to restitution.Keywords: Protection of Child Victims; Consideration Requisitor Public Prosecutor;  Restitution